DUKUNGAN PEMERINTAH DALAM PENUMBUHAN SIKAP PETANI TERHADAP IMPLEMENTASI SUBSIDI BUNGA PERTANIAN DI JAWA TENGAH - Sholikhati, Anniyatis (Badan Riset dan Inovasi Daerah Provinsi Jawa Tengah, 2023)
In order to support the National Economic Recovery (PEN) program in dealing with the impact of the COVID-19 pandemic, the Provincial Government of Central Java provides financial assistance to farmers to increase productivity and welfare of farmers, especially small farmers who have limited land with maximum land area of 1 (one) hectare and provides credit facilitation for commodity cultivation farming (on a farm). This government support is realized in the form of an interest subsidy program for agricultural sector loans to be implemented in 2022. This paper aims to 1) describe the implementation of the loan interest subsidy program in the agricultural sector between targets, achievements, program technical guidelines, and obstacles in program implementation; 2) analyze the factors of government support in influencing farmers' attitudes towards the loan interest subsidy program and its effect on the empowerment of farmers in Central Java Province. The research method used was a census using a questionnaire as a data collection instrument. The research locations were carried out in three districts as pilot project locations for the agricultural sector loan interest subsidy program in Central Java. Respondents are farmers who have received information about the interest subsidy program. The study results show that the support factor of the government has a significant influence on farmers' attitudes toward implementing the interest subsidy program. The author recommends that the government continue to provide adequate support for the interest subsidy program for agricultural sector loans in Central Java. This support can be in the form of providing clear and easy-to-understand information about the program, providing an adequate budget, good cooperation with financial institutions, providing guidance and assistance in program implementation. In addition, the government also needs to improve inter-agency coordination and encourage collaboration between stakeholders to strengthen the interest subsidy program. Keywords: farmer attitude. interest subsidy